(c) 5q2 - p2 - 7r from 6p2 - q2 + 2r
(d) - x - y from. x + y
Answers
Answered by
1
Answer:
7p2-6q2+9r
Step-by-step explanation:
6p2-q2+2r-(5q2-p2-7r)
=6p2+p2-q2+2r-5q2+p2+7r
=6p2+p2-q2-5q2+2r+7r
=7p2-6q2+9r
ANSWER:
d. x+y-(-x-y)
=x+y+x+y
=x+x+y+y
=2x+2y
Answered by
5
Answer:
Hope you like the answer plz mark me brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d1a/1541084ed66c1ab891793f1e7eb4b14a.jpg)
![](https://hi-static.z-dn.net/files/db2/c6bb49eccd31c2eaf4cc0e8ac69f8746.jpg)
Similar questions
English,
2 months ago
Computer Science,
2 months ago
India Languages,
2 months ago
Math,
5 months ago
Environmental Sciences,
5 months ago
Math,
11 months ago
English,
11 months ago